INTERVENTION PROGRAM IN EFFORT TO REDUCE NEW CASES OF LUNG TUBERCULOSIS IN TELUKNAGA - Edwin Destra; Yohanes Firmansyah (Bajang Institute, 2022)
Introduction: According to the WHO, tuberculosis (TB) will be the world's 13th largest cause of death in 2020. Indonesia is the third biggest country in terms of new tuberculosis cases, having reached 845,000 cases. In Indonesia, the number of new cases continues to rise, and there are still incidents of treatment discontinuation and undiscovered infection. Objective: Reduce new tuberculosis cases at Teluknaga Health Center. Method: The study assesses participants using a pre- and post-test, with interventions in the form of counseling and demonstrations of proper cough etiquette to raise public awareness. Non-random consecutive sampling was used to select the sample. The intervention used to improve public awareness is the independent variable in this study. The dependent variable in this study is knowledge change. Result:, 30 respondents reported a gain in their knowledge in ten specified areas regarded to be indications of expertise. Conclusion: Interventions in the form of tuberculosis counseling and cough etiquette, as well as cough demonstrations, have successful in boosting public awareness of pulmonary tuberculosis. It is hoped that changes in people's attitudes and behaviors would occur in order to prevent tuberculosis infection from spreading throughout the community.